Sustainable Development Goals : Tinjauan Percepatan Pencapaian Di Provinsi Riau - Eko Handrian; Hendry Andry (UIR Press, 2020)
The description of poverty in Riau Province, there are several regions with high poverty rates, including Meranti Islands District (33.85%) and Pelalawan (11.15%). The preparation of the Riau Provincial Regional Action Plan is a form of commitment to accelerate development and priority development programs in Riau Province which have not been previously achieved in the MDGs marked by the issuance of Governor Regulation No. 33 of 2018 dated 5 June 2018 concerning RAD TPB / SDGs in 2017-2019 . This research is a literature study, participatory and inclusive approach is the principle of implementing SDGs carried out in each stage of the regional action plan of Riau province. The integration of the RPJMD and RAD in Riau Province is the focus of acceleration in achieving the SDGs goals by synchronizing the SDGs objectives with the objectives of the Riau RPJMD. The SDGs' priorities are based on how big the problems are in the regions, the SDGs-related agenda refers to the national plan, the approach used by local governments that the idea of development is a support for regional development priorities in line with the vision and mission of the regional head. In addition, synchronization and acceleration of the implementation of SDGs need to be built in institutions including structures, coordination and communication mechanisms, information sharing, monitoring and evaluation.